2022
DOI: 10.1128/mbio.02068-22
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Genotype Is a Major Predictor of Mortality from Visceral Leishmaniasis

Abstract: Multiple factors contribute to the risk of mortality from visceral leishmaniasis (VL), including, patient genotype, comorbidities, and nutrition. Many of these factors are influenced by socioeconomic biases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…These observations offer clues for investigation to explain why L. donovani variants cause human cutaneous leishmaniasis instead of VL in Sri Lanka [ 29 ]. Finally, whole-genome sequence analyses of 109 L. infantum isolates found parasite sequences that are strongly associated with the phenotypes of disease severity, such as mortality and kidney failure [ 30 ]. However, observations on the early preclinical events in human infection will be needed to fully understand the important question of how the disease is initiated.…”
Section: Infectionmentioning
confidence: 99%
“…These observations offer clues for investigation to explain why L. donovani variants cause human cutaneous leishmaniasis instead of VL in Sri Lanka [ 29 ]. Finally, whole-genome sequence analyses of 109 L. infantum isolates found parasite sequences that are strongly associated with the phenotypes of disease severity, such as mortality and kidney failure [ 30 ]. However, observations on the early preclinical events in human infection will be needed to fully understand the important question of how the disease is initiated.…”
Section: Infectionmentioning
confidence: 99%
“…Similar observations have been made in the fields of bacteriology and parasitology. Escherichia coli genotypes exhibit a spectrum of disease severity ranging from asymptomatic to severe, and parasite genotype explains 83% of the variation in mortality from visceral leishmaniasis [4][5][6]. Yet we know little about the impact of helminth genetic variation on disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…While most data suggests that parasite isolates from cutaneous and mucosal CL from the same patients are genetically very similar (11, 12), most of this work has relied on experimental characterisation of small numbers of parasite isolates taken from cases with differing clinical presentations. While whole-genome data from natural populations of many Leishmania species is now available (e.g (1316)), there has been little work directly attempting to directly relate parasite genetic variation to clinical variation. One exception is a recent genome-wide association study that found some evidence that clinical outcome is linked to parasite genotype in L. infantum (16).…”
Section: Introductionmentioning
confidence: 99%
“…While whole-genome data from natural populations of many Leishmania species is now available (e.g (1316)), there has been little work directly attempting to directly relate parasite genetic variation to clinical variation. One exception is a recent genome-wide association study that found some evidence that clinical outcome is linked to parasite genotype in L. infantum (16). Research on L. aethiopica is particularly neglected, and the only genomic data available for this species is from 19 historical isolates and some hybrid forms collected from cryopreserved culture collections (17).…”
Section: Introductionmentioning
confidence: 99%